The impact of a national carbon price on China. Issue 4 (15th October 2021) - Meng, Samuel; Siriwardana, Mahinda; Shen, Ying
Abstract: As the world No.1 emitter of carbon dioxide (CO2 ), China has made up its mind to act on climate change. After trials in six pilot regions- Shenzhen, Shanghai, Beijing, Guangdong, Tianjin, Hubei, and Chongqing- a nationwide ETS has been established and implemented in line with the Thirteenth Five-Year Plan period (2016–2020). This paper simulates the effect of a national ETS in China using GTAP 9.1 database and a revised GTAP-E model. The simulation results show that the ETS is very effective in emissions reduction but will cause a mild economic contraction. At the sectoral level, the energy and resource sectors and energy intensive sectors are to be hit hard while most other sectors are affected negatively but insignificantly.